2010
DOI: 10.1149/1.3485688
|View full text |Cite
|
Sign up to set email alerts
|

Niobium Contamination in Silicon

Abstract: In this paper niobium is characterized as a silicon contaminant. It is shown that niobium is a relatively slow diffuser, with an intermediate diffusivity between very slow diffusers such as molybdenum and fast diffusers such as iron. Niobium is found to be very effective as a recombination center, and in addition prone to surface segregation. In addition, niobium shows optical activation, but no thermal activation. Three deep levels are revealed in niobium contaminated silicon, plus an additional level observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Subsequent work mainly by deeplevel transient spectroscopy (DLTS) showed that early TMs are electrically active and responsible for several deep levels in the gap (see for example Refs. [1,2,5,6] and references therein). It is, therefore, of primary interest to be able to determine accurately the signature of these TMs, in particular, the location of their electrical levels in the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent work mainly by deeplevel transient spectroscopy (DLTS) showed that early TMs are electrically active and responsible for several deep levels in the gap (see for example Refs. [1,2,5,6] and references therein). It is, therefore, of primary interest to be able to determine accurately the signature of these TMs, in particular, the location of their electrical levels in the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Metal surface segregation: the example of niobium. In a previous work [3] we showed that niobium is very prone to surface segregation. Evidence of surface segregation even after a RTA treatment was given by surface photovoltage, Elymat and DLTS, showing that with 10 12 cm -2 dose less than 10% of the dose was in the solid solution.…”
Section: Resultsmentioning
confidence: 84%
“…Low doses (10 11 cm -2 to 10 12 cm -2 ) were considered, in order to limit ourselves to realistic contamination levels in non-optimum process conditions. Niobium was implanted at the wafer front side, because in a previous study it was shown to be a slow diffuser [3], so it could not reach the opposite side of the wafer with a reasonable thermal treatment. The samples were oxidized to 1000 Å and implanted with 1 MeV energy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For these contaminants, a generation lifetime in the range 10 −3 -10 −2 s corresponds to a concentration of the order of 10 10 cm −3 . 20,21 In this work the capacitors were pulsed from flatband voltage conditions to ±5 V deep depletion conditions, and the steady state recovery was recorded by measuring the capacitance with 100 kHz frequency signal. To limit perimeter effects, square capacitors with 2.25 mm 2 area were used for these measurements.…”
Section: Experimental Techniques-surface Photovoltage (Spv)-mentioning
confidence: 99%